Are females more variable than males in gene expression? Meta-analysis of microarray datasets. Issue 1 (December 2015) - Itoh, Yuichiro; Arnold, Arthur
Abstract Background The majority of preclinical biomedical research involves studies of males rather than females. It is thought that researchers have avoided females based on the idea that female traits are more variable than those of males because of cyclic variation in effects of ovarian hormones. Methods To test the assumption of inherently greater female variability, we analyzed 293 microarray datasets measuring gene expression in various tissues of mice and humans, comprising analysis of more than 5 million probes. Results Meta-analysis showed that on average, male gene expression is slightly more variable than that of females although the difference is small. We also tested if the X chromosome of humans shows greater variability in gene expression in males than in females, as might be expected because of hemizygous exposure of polymorphic X alleles but again found little sex difference. Conclusion Our analysis supports and extends previous studies reporting no overall greater phenotypic variability in females.